Pengembangan Game Maze Berbantu Program Scratch Untuk Meningkatkan Kemampuan Pemecahan Masalah Anak usia 5-6 Tahun - Lily Permatasari (Prosiding University Research Colloquium, 2021)
In this study, a "maze game" was developed as a medium to stimulate problemsolving abilities of children aged 5-6 years. This study aims to describe the developmentprocess, feasibility, and effectiveness of game maze as a medium for stimulating problemsolving abilities of children aged 5-6 years. The maze game development model refers tothe ADDIE development model with the following stages: 1) analysis, 2) design, 3)development, 4) implementation and 5) evaluation. The results of this study indicate thatMaze Game was made with Scratch 3.0 software consists of 16 levels with tiered difficultylevels. Maze Game can be run on a computer or laptop with a windows operating system.Maze Game was declared suitable for use based on the results of the assessment of thequality of the games tested on media experts which could be categorized as very feasiblewith a feasibility percentage of 80.26%, Material test assessments on material expertsobtained very decent results with a feasibility percentage of 77.94%, and practitionerassessments were categorized as very feasible with a feasibility percentage of 88.24%. Theresults of the analysis show that the use of maze games is effective in improving problemsolving abilities of children aged 5-6 years.